From Melanoma Development to RNA-Modified Dendritic Cell Vaccines: Highlighting the Lessons From the Past - Shadbad, Mahdi Abdoli; Hajiasgharzadeh, Khalil; Derakhshani, Afshin; Silvestris, Nicola; Baghbanzadeh, Amir; Racanelli, Vito; Baradaran, Behzad (Frontiers in Immunology, 2021)
Although melanoma remains the deadliest skin cancer, the current treatment has not resulted in the desired outcomes. Unlike chemotherapy, immunotherapy has provided more tolerable approaches and revolutionized cancer therapy. Although dendritic cell-based vaccines have minor side effects, the undesirable response rates of traditional approaches have posed questions about their clinical translation. The immunosuppressive tumor microenvironment can be the underlying reason for their low response rates. Immune checkpoints and indoleamine 2,3-dioxygenase have been implicated in the induction of immunosuppressive tumor microenvironment. Growing evidence indicates that the mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase/Protein kinase B (PKB) (PI3K/AKT) pathways, as the main oncogenic pathways of melanoma, can upregulate the tumoral immune checkpoints, like programmed death-ligand 1. This study briefly represents the main oncogenic pathways of melanoma and highlights the cross-talk between these oncogenic pathways with indoleamine 2,3-dioxygenase, tumoral immune checkpoints, and myeloid-derived suppressor cells. Moreover, this study sheds light on a novel tumor antigen on melanoma, which has substantial roles in tumoral immune checkpoints expression, indoleamine 2,3-dioxygenase secretion, and stimulating the oncogenic pathways. Finally, this review collects the lessons from the previous unsuccessful trials and integrates their lessons with new approaches in RNA-modified dendritic cell vaccines. Unlike traditional approaches, the advances in single-cell RNA-sequencing techniques and RNA-modified dendritic cell vaccines along with combined therapy of the immune checkpoint inhibitors, indoleamine 2,3-dioxygenase inhibitor, and RNA-modified dendritic cell-based vaccine can overcome these auto-inductive loops and pave the way for developing robust dendritic cell-based vaccines with the most favorable response rate and the least side effects.